Patients’ perception of service quality in a healthcare not-for-profit organisation - Melene Strauss; Renata Schoeman (South African Family Practice)
Background: Service organisations should be aware of those elements that are perceived as excellent quality and incorporate these as part of their service offering. However, a not-for-profit (NPO) healthcare organisation consists of a diverse group of stakeholders who have different perspectives and interests. Service quality therefore requires a multidimensional definition that comprehends all their needs and expectations.